Квітниково-декоративні рослини в гірських садово-паркових ландшафтах - Tatarchuk, R.Ya.; Кuznentsov, S.I.; Kazanskaya, N.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2012)
The data on introduction potential of species diversity of herbaceous plants for mountain garden and park landscapes are given.